"All are welcome here?": Navigating race, class, gender, sexual orientation, age, and disability in American feminist coffeehouses of the 1970s and 1980s. Issue 2 (24th December 2020) - Ketchum, Alex D.
Abstract: In the 1970s and 1980s, feminists in the United States began businesses in order to financially support themselves while enacting women's movement politics. Owning and operating a feminist business in a permanent location required large capital investment in order to rent space, buy supplies, and pay workers. Women's, and especially lesbians', social positioning due to discriminatory gender, racial, and sexual orientation laws affected whether or not being able to own a restaurant or store was even possible. Coffeehouses provided an alternative means through which to build feminist communities, with lower initial capital required than restaurants. Feminist coffeehouses in this article will primarily refer to recurring temporary public spaces that served refreshments and provided entertainment. This model of feminist organization expanded participation in some ways; without high fixed costs, coffeehouses enabled women with less money, women from marginalized racial groups, and women with marginalized sexual orientations the ability to create spaces centered on food, drink, and socializing. However, these spaces were not utopic; racism, ageism, trans‐exclusionism, and classism created tension in their respective communities. As coffeehouse organizers tried to address various inequalities, their approach in treating each identity category as discrete often erased women who experienced multiple forms of oppressions simultaneously.